Point cloud georeferencing - Wilson (Nanyang Technological University, 2024)
The process of associating spatial coordinates with geographic data, also known as Georeferencing is extremely important in the current industry, and it plays a crucial role in various fields such as in building information modelling (BIM), remote sensing, and underground mining. This study investigates the principles and methodologies of georeferencing and applying the techniques in BIMBot. The research begins with an overview of the way Global Positioning System (GPS) works and methods on collating a type of spatial data, which is the point cloud data using LiDAR and GPS module. The study also examines the importance of automation and difference between using software to georeference and using script for automation. Both of which aims to generate a transformation matrix that can be used to transform the local point cloud data. Furthermore, methods used for coordinate transformation and rigid body motion were also examined in order to find effective and easy to use method for georeferencing using method that are currently not used in the industry. Lastly, integration between the software and hardware systems of BIMBot were explored and methods to connect all the different hardware modules were made by the use of Robot Operating Systems (ROS). And finally, the report ends with the conclusions, limitation and also the recommendation for future work on this project.